CONTROLLED GROWTH OF IRON OXIDE MAGNETIC NANOPARTICLES VIA CO-PRECIPITATION METHOD AND NaNO3 ADDITION - Grace Tj. Sulungbudi; Yuliani Yuliani; Wildan Zakiah Lubis; Sri Sugiarti; Mujamilah Mujamilah (Jurnal Sains Materi Indonesia, 2017)
Size controlled magnetic nanoparticle (MNPs) of iron oxide were prepared in the presence of NaNO3 via co-precipitation method followed by HNO3 peptizing according to Massart’s method. The MNPs size were reduced by addition of NaNO3 in varied molarity and at different stage of process. As an end product, stable water-base colloids were formed. XRD pattern analysis using Rietveld method confirmed Fe3O4/g-Fe2O3 phase formation with nanoscale crystallite size. This crystallite size significantly decrease with NaNO3 addition from 12 nm to smaller than 8 nm, and give end-result of decreasing magnetization as measured by VSM. Langevin fitting of magnetic hysteresis curve also revealed the magnetic core size of nearly the same behaviour. TEM results show bigger value for single magnetic nanoparticle of > 10 nm and < 10 nm for MNPs without and with NaNO 3 addition, respectively. However, PSA measurement still trace a low nanoparticle agglomeration of ~ 20 nm, even after surface peptization using HNO3. A possible mechanism is proposed to explain these characteristics formation especially of the MNP’s size.